Evaluasi Metode Audit Penghitungan Kerugian Keuangan Negara pada Badan Pengawasan Keuangan dan Pembangunan - Situmeang, Unjur Marroha; Susanto, Dwi Setiawan (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to evaluate the audit method for Calculating State Financial Losses (PKKN) by the Financial and Development Supervisory Agency (BPKP). PKKN audit results by BPKP are still not accepted or corrected by the Court. This research method is qualitative, with an evaluation approach using case studies at BPKP. The primary data used in this research are the results of interviews with BPKP auditors who have carried out PKKN audits and are experts in court. The trial decision document will be mapped based on case description themes, PKKN methods, and PKKN values. The secondary data used is a copy of the court decision on a criminal corruption case that was finalized and downloaded from the official website of the Supreme Court (MA). The implementation of the PKKN audit by BPKP is evaluated using a fraud theory approach, the REAL Tree concept, and applicable laws and regulations. The provision of expert testimony in court will be considered using the Daubert test. The results of this research are that the PKKN audit by BPKP does not follow the fraud theory approach because it does not create and test hypotheses. There is a PKKN method that differs from the REAL Tree concept because BPKP auditors apply the criteria for real and definite state financial losses (actual loss) without considering compelling interest as a time value of money concept. Providing expert information by BPKP auditors is different from the Daubert test because BPKP does not require monitoring and evaluating court decisions and does not carry out peer reviews of PKKN methods.